2012
DOI: 10.1111/1556-4029.12044
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Diabetic Ketoacidosis and Antipsychotic Medication

Abstract: Hyperglycemia and new onset diabetes have been described with certain antipsychotic medications and some of the initial presentations are fatal diabetic ketoacidosis (DKA). We report 17 deaths due to DKA in psychiatric patients treated with second generation antipsychotic medications. Death certificates and toxicology data were searched for DKA and hyperglycemia. We reviewed the medical examiner records which included the autopsy, toxicology, police, and medical examiner investigators' reports. The decedents r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…It is worthwhile to note that some antipsychotic medications, especially quetiapine and olanzapine, have been associated with acute onset of hyperglycemia and ketoacidosis [ 51 ]. Cognitive dysfunction associated with elevated glucose levels may be mistaken for the patient's baseline cognitive deficit resulting in delay in detection of hyperglycemia.…”
Section: Treatment Of Diabetes In Schizophreniamentioning
confidence: 99%
“…It is worthwhile to note that some antipsychotic medications, especially quetiapine and olanzapine, have been associated with acute onset of hyperglycemia and ketoacidosis [ 51 ]. Cognitive dysfunction associated with elevated glucose levels may be mistaken for the patient's baseline cognitive deficit resulting in delay in detection of hyperglycemia.…”
Section: Treatment Of Diabetes In Schizophreniamentioning
confidence: 99%
“…The APA guidelines, list SDAs as the first choice for acute treatment (3); however, these drugs are associated with the side effect of glucose intolerance (4-9). This may occasionally trigger a hyperglycemic crisis, and some fatal cases have been reported (5,10-12). The mechanisms underlying the onset of glucose intolerance are reported to be as follows.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are listed in the American Psychological Association (APA) guidelines as the first choice in acute phase treatment (3). However, one side effect of these SDAs is glucose intolerance (4-9), which occasionally causes a hyperglycemic crisis, and a few fatal cases have been reported (5,10-12). There are no reports of these drugs being associated with the onset of type 1A diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ely et al 2 reported 17 deaths due to diabetic ketoacidosis in psychiatric patients treated with second-generation antipsychotics. Quetiapine was the most frequently suspected agent.…”
Section: Discussionmentioning
confidence: 99%